Florida's Introduced Birds: Monk Parakeet (Myiopsitta monachus) - Steve A. Johnson; Sam Logue (EDIS)
WEC-257, a 6-page illustrated fact sheet by Steve A. Johnson and Sam Logue, introduces this small to medium-sized member of the parrot family that has become an established non-native bird in Florida — species description, similar species, native range and habitats, mode of introduction, introduced range and habitats, ecology, ecological impacts, impacts on people and pets, solutions, and how you can help. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, June 2009.